The effect of blocked vision on the reproducibility of ballet leg positions in elite synchronized swimmers - Komori, Y.; Kamiyoshi, M.; Onishi, H.; Shimura, Y. (The Journal of Physical Fitness and Sports Medicine, 2016)
Introduction Synchronized swimming competition includes a figure session and a routine session. All specified 200 figures are constituted from movements of the leg, such as hip extension flexion movements. In particular, the ballet leg positions (from a back layout position to raise a leg and to keep the hip flexion angle at 90 degree) account for 40% of the figures. Therefore, precise control of hip flexion angle is important for synchronized swimmers. The purpose of this study was to examine the effect of blocking a swimmer`s vision on the reproducibility of ballet leg positions among elite junior and senior synchronized swimmers. Methods A total of 24 elite female synchronized swimmers participated in this study. The participants were divided into the following 2 groups: junior groupand senior group. The participants performed the ballet leg positions under normal visual conditions and also with vision blocked, in water and on dry land. The repositioning error (RE) of the hip flexion angle was evaluated using an image analyzing system with high speed video cameras. Results and discussion In water and on land, there were no differences in the RE for achieving the ballet leg position under blocked or normal visual conditions in either age group.These findings showed that the precise reproducibility of ballet leg position was not correlated with vision either in water or on dry land. Elite synchronized swimmers are able to achieve high reproducibility of ballet leg positions without reliance on visual cues.